A Global Macroeconomic Risk Model for Value, Momentum, and Other Asset Classes. (13th February 2022) - Cooper, Ilan; Mitrache, Andreea; Priestley, Richard
Abstract: Value and momentum returns and combinations of them across both countries and asset classes are explained by their loadings on global macroeconomic risk factors. These loadings describe why value and momentum have positive return premia, although being negatively correlated. The global macroeconomic risk factors also perform well in capturing the returns on other characteristic-based portfolios. The findings identify a global macroeconomic source of the common variation in returns across countries and asset classes.